Booklet handout to improve glycemic control in type-2-DM patients and comparison with other models - Daniek Viviandhari; Nora Wulandari; Nur Rahmi (Universitas Ahmad Dahlan, 2021)
Non-adherence is still a major issue in the management of diabetes in Indonesia which leads to complication problems. Medication adherence in diabetes mellitus is related to better glycemic control, better control of risk factors, lower risk of hospitalization, lower health care cost, and lower risk of mortality. Many educational models are applied to achieve the patient's glycemic control. There were two research purposes in this study. The first one was to determine the booklet handout's effectiveness in improving glycemic control in type-2 diabetes mellitus patients in Malaka Jaya Primary Healthcare Centre, Jakarta. The second aim was to compare two different educational models, which were done simultaneously at Pondok Kelapa Primary Healthcare Centre and Duren Sawit Primary Healthcare Centre. A quasi-experimental study design was applied in these prospective studies. A total of 30 patients met the inclusion criteria. The intervention was a booklet handout that was given and presented to the respondent once every month for three months. The parameter used was the A1C (glycated hemoglobin). For patients exposed to booklet handout, 20.0% of them had the A1C level <6.5% initially, then the A1C level <6.5% significantly increased to 73.34% (p=0.005). For patients who were given public counseling, the number of respondents who had the A1C level <6.5% was 16.7%, then the A1C percentage rose to 76.7% (p=0.005). Meanwhile, for patients who were educated with video, the A1C level <6.5% was 6.67% initially, then the A1C level <6.5% increased significantly to 90.0% (p=0.005) in 12 weeks after the intervention. Either booklet handout, public counseling, or video are effective to improve glycemic control in type-2 diabetes mellitus patients.